Mapping Intestinal Worm Infections and Their Relationship with Nutritional Status and Personal Hygine of School Age Children in Wori District, North Minahasa Regency - Lalangpuling, Indra Elisabet; Pascoal, Kevin G.; Rantesalu, Agnes; Sula, Ibrahim Pandu (UNUSA Press, 2025)
Introduction: Parasitic infections cause health problems, including diarrhea, abdominal pain, malnutrition, general malaise and weakness, as well as impaired physical growth and development. These parasitic infections are generally higher in countries with high Factors that influence public health problems include weak economic conditions, limited access to sanitation and clean water, high rates of malnutrition among the population, population density, community habits that do not meet hygiene standards, low levels of education, and mothers' minimal insight into health. Objective: This study aims to identify the distribution of intestinal worm infections in school-age children in Wori District, North Minahasa Regency, and to analyze the relationship between these infections and children's nutritional status and the implementation of clean and healthy living behaviors (PHBS). Methods: A quantitative approach was used, integrating statistical analysis and distribution mapping. The study took place from January 2023 to May 2024, involving 14 elementary schools and 309 students selected via random sampling. Statistical analysis assessed the relationship between worm infections, nutritional status, and PHBS indicators. Results: The study results indicated that respondents were infected with Ascaris lumbricoides and hookworm. Statistical tests showed a statistically significant association between infection incidence and handwashing habits and twice-daily bathing frequency, with a p-value <0.005. Conclusions: Based on research findings, intestinal worm infections in elementary school children were identified in all village areas in Wori District, with the exception of Lansa Village which did not show any cases of infection. No significant association was found between intestinal worm infections and children's nutritional status. However, there was a statistically significant association between infection incidence and handwashing and bathing twice daily.